2007
DOI: 10.1128/mcb.02116-06
|View full text |Cite
|
Sign up to set email alerts
|

Drp1 Mediates Caspase-Independent Type III Cell Death in Normal and Leukemic Cells

Abstract: Ligation of CD47 triggers caspase-independent programmed cell death (PCD) in normal and leukemic cells. Here, we characterize the morphological and biochemical features of this type of death and show that it displays the hallmarks of type III PCD. A molecular and biochemical approach has led us to identify a key mediator of this type of death, dynamin-related protein 1 (Drp1). CD47 ligation induces Drp1 translocation from cytosol to mitochondria, a process controlled by chymotrypsin-like serine proteases. Once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
117
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 91 publications
4
117
0
Order By: Relevance
“…1 Ligation of CD47 is known to induce apoptotic and nonapoptotic death in several cell types including activated T cells, 39 B-cell chronic lymphocytic leukemia, 40,41 promyelocytic leukemia, 42 multiple myeloma, 43 breast carcinoma, 44 and monocytes and dendritic cells. 45 Jurkat T cells deficient of CD47 are resistant to Fas-mediated cell death and are sensitized to death by ligation of Fas and re-expression of CD47.…”
Section: ) (D) Wt Cd47mentioning
confidence: 99%
“…1 Ligation of CD47 is known to induce apoptotic and nonapoptotic death in several cell types including activated T cells, 39 B-cell chronic lymphocytic leukemia, 40,41 promyelocytic leukemia, 42 multiple myeloma, 43 breast carcinoma, 44 and monocytes and dendritic cells. 45 Jurkat T cells deficient of CD47 are resistant to Fas-mediated cell death and are sensitized to death by ligation of Fas and re-expression of CD47.…”
Section: ) (D) Wt Cd47mentioning
confidence: 99%
“…In addition to steadystate activity, Drp1 is also associated with early apoptosis (4,(7)(8)(9)(10). Cellular stress increases Drp1 shuttling, which leads to fragmented mitochondrial networks, whereas prolonged or severe insult promotes stabilization of Drp1 to the mitochondria, which increases the likelihood of progression to apoptotic cell death (7,8,(11)(12)(13). Phosphorylation of Drp1-S637 prevents translocation to mitochondria, whereas overexpression of Drp1 K38A (a dominant-negative mutation lacking GTPase activity) prevents Drp1 translocation, attenuates a fragmented mitochondrial phenotype, and decreases cell death (4,14).…”
mentioning
confidence: 99%
“…5 In this study, we reported that the engagement of CD47 efficiently killed CLL cells. CD47 is a glycoprotein composed of a single IgV-like extracellular domain, a transmembrane region and a short intracytoplasmic tail.…”
mentioning
confidence: 95%
“…These molecules regulate a variety of biological phenomena in the immune system, such as platelet activation, leukocyte and dendritic cell migration, macrophage multinucleation and cell death. Concerning PCD, we reported in our recent paper that CD47-mediated type III PCD is exclusively characterized by cytoplasmic hallmarks, 5 including an exposure of phosphatydilserine in the outer leaflet of the plasma membrane, a decrease in mitochondrial transmembrane potential (DC m ) and reactive oxygen species production. Caspase-independent type III PCD involves the serpases, a family of serine proteases, and is related to the mitochondrial redeployment of the cytosolic protein Drp1.…”
mentioning
confidence: 99%